Wallace H. White papers - White, Wallace H. (Wallace Humphrey), 1877-
Correspondence, speeches, reports, articles, legislation file, scrapbooks, printed matter, sound recording, and other papers relating chiefly to White's service as a U.S. representative (1917-1931) from Maine. Subjects include commerce, communications, conservation, fisheries, immigration, interstate commerce, maritime issues, merchant marine, military policy, national defense, neutrality, the Passamaquoddy Tidal Project, the Saint Lawrence Seaway, taxes, tariffs, and veterans' affairs. Correspondents include Newton Diehl Baker, Owen Brewster, Carrie Chapman Catt, Bainbridge Colby, Josephus Daniels, Warren G. Harding, Herbert Hoover, Charles Evans Hughes, Cordell Hull, Franklin K. Lane, Robert Lansing, and Medill McCormick.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. representative and senator from Maine.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Brewster, Owen, -- 1888-1961 -- Correspondence; Catt, Carrie Chapman, -- 1859-1947 -- Correspondence; Colby, Bainbridge, -- 1869-1950 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Lane, Franklin K. -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; McCormick, Medill, -- 1877-1925 -- Correspondence; United States. -- Congress. -- House; Bays -- Maine; Communication -- United States; Conservation of natural resources -- United States; Fisheries -- United States; Hydroelectric power plants -- Maine; Interstate commerce -- United States; Maritime concerns -- United States; Merchant marine -- United States; Military policy -- United States; Military readiness; Neutrality -- United States; Tariff -- United States; Taxation -- United States; Tidal power; Veterans -- United States; Waterways -- North America; Maine -- Politics and government; Passamaquoddy Bay (N.B. and Me.); Saint Lawrence Seaway; United States -- Commerce; United States -- Defenses; United States -- Emigration and immigration; United States -- Politics and government -- 1901-1953.; Representatives, U.S. Congress -- Maine; Senators, U.S. Congress -- Maine